2003
DOI: 10.1093/ps/82.10.1589
|View full text |Cite
|
Sign up to set email alerts
|

Guar meal germ and hull fractions differently affect growth performance and intestinal viscosity of broiler chickens

Abstract: High concentrations of guar meal in poultry diets deleteriously affect growth, feed intake, and digesta viscosity. These effects are attributed to residual gum in the meal. A 2 x 5 factorial experiment investigated the impacts of two guar meal fractions (germ and hull) at five inclusion levels (0, 2.5, 5.0, 7.5, and 10.0%) on intestinal viscosity, measures of growth, and feed conversion in broiler chickens fed to 20 d of age. Growth and feed conversion ratio were not affected by inclusion of as much as 7.5% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 13 publications
9
51
0
Order By: Relevance
“…Similar results were also reported by Lee et al (2003). They reported that guar meal, administered in doses of 2.5% and 5% in feeds, had no negative effects on the growth performances of broiler chickens, whereas higher doses (7.5 and 10%) negatively influenced both growth performances and broiler chicken health.…”
Section: Introductionsupporting
confidence: 87%
“…Similar results were also reported by Lee et al (2003). They reported that guar meal, administered in doses of 2.5% and 5% in feeds, had no negative effects on the growth performances of broiler chickens, whereas higher doses (7.5 and 10%) negatively influenced both growth performances and broiler chicken health.…”
Section: Introductionsupporting
confidence: 87%
“…In the study by Lee et al (2003a), the hull fraction of gaur increased intestinal viscosity at all inclusion levels fed (0, 2.5, 5.0, 7.5 and 10.0%). In their investigation, although FCR was not affected until the inclusion rate exceeded 5.0%; whereas, the germ fraction significantly increased intestinal viscosity at 7.5 and 10% inclusion rates.…”
Section: Discussionmentioning
confidence: 83%
“…Some studies reported that there was no negative impact on productive performance after adding GM without enzyme to diets at concentrations up to 2.5% in broiler chicks (Lee et al, 2003a;2003b) or 5% in laying hen diets (Gutierrez et al, 2007). Different indigestible polysaccharides, such as pectin, gum Arabic, gum agar, locust bean gum and guar gum, increase intestinal viscosity, which decreases growth and increases feed conversion.…”
Section: Discussionmentioning
confidence: 99%
“…However, guar bean contains some anti-nutritional factors like trypsin inhibitor and a galactomannan (guar gum) which affect feed conversion ratio and growth performance in broilers (Saxena and Pradhan, 1974). Diets supplemented with guar bean increases intestinal viscosity due to β-galactomannan leading to reduced nutrient digestibility especially in a day old chickens (Lee et al, 2003;Abu Hafsa et al, 2017). This increase in the intestinal viscosity has also a negative effect on passage rate resulting in poor feed intake (Yasar, 2003).…”
Section: Anti-nutritional Factors Of Guar Mealmentioning
confidence: 99%